Economic Feasibility of Material Waste Management “Reduction, Reuse, Recycle and Repair’ Strategies in Egypt’s Footwear Industry - Motawea, Amira (AUC Knowledge Fountain, 2024)
The study aims to provide a comprehensive examination of the feasibility of waste management strategies in the leather and footwear industry, both globally and within the specific context of Egypt. It explores the benefits and challenges associated with efficiently recycling, treating, or reusing material waste generated by the footwear industry, with a particular focus on Egypt. The study begins by discussing established waste management practices in the global fashion industry and focusing on footwear material waste. The study examines successful waste management methods and systems employed globally, highlighting their potential applicability to the Egyptian fashion sector. A key aspect of the study involves an in-depth analysis of the current state of waste generation within Egypt's footwear industry and the existing waste management practices. By quantifying the volume of waste generated and examining how waste is presently handled, the study seeks to determine the potential environmental and economic impacts of introducing new waste management methods. The primary objective of this exploratory study is to understand the behavior of the factory managers to determine their willingness to do the change and analyze waste management practices to recommend strategies for optimizing implementation. Another important aim is to propose a robust and integrated system for material waste management that involves collaboration between multi stakeholders. This proposed system includes the collection of waste from manufacturing facilities and the subsequent categorization of materials and waste made by intermediaries specialized in waste collection. Specialized recycling companies would then apply their expertise to either recycle, reuse, or treat the waste effectively. Furthermore, the study emphasizes the importance of designing a framework of material waste management practices in the footwear industries which not only addresses environmental concerns but also incorporates monetization strategies or incentives to promote a unified process to manage material waste from the footwear industries in Egypt. This approach aims to create a financial incentive for stakeholders to actively participate in the waste management process. Ultimately, the main goal is to develop a 360-degree framework of sustainable practices for waste management tailored to the unique characteristics of the footwear industry in Egypt. This framework would encompass waste reduction, efficient recycling, economic benefits, and environmental preservation. By achieving this goal, the footwear industry in Egypt can move toward a more sustainable and environmentally responsible future while also fostering economic growth and collaboration among stakeholders.